Advances in mechanical engineering : selected contributions from the Conference "Modern Engineering: Science and Education", Saint Petersburg, Russia, June 20-21, 2013 /: selected contributions from the Conference "Modern Engineering: Science and Education", Saint Petersburg, Russia, June 20-21, 2013. (2015) - Unknown
No abstract available